PENGARUH JENIS BARANG DAGANGAN, JAM KERJA DAN MODAL USAHA TERHADAP PENDAPATAN PEDAGANG DI PASAR AGUNG PENINJOAN KOTA DENPASAR - Mega Pratiwi, I Gusti Agung Mas; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 9 (2021): VOL 10 NO 9, SEPTEMBER 2021 [3528 - 3965], 2021)
The objectives of this study are 1) To analyze the effect of types of merchandise, working hours and working capital simultaneously on the income of traders in Pasar Agung Peninjoan Denpasar City 2) To analyze the effect of types of merchandise, working hours and working capital partially on the income of traders in Pasar Agung Peninjoan Denpasar City. The number of samples taken was 77 respondents. The analysis technique used is multiple linear regression. Based on the analysis, it is found that the type of merchandise, working hours and working capital simultaneously have a positive and significant effect on income. Types of merchandise, working hours and working capital partially have a positive and significant effect on income. Traders who sell types of primary necessity merchandise dominantly influence income, because they have higher income than traders who sell types of secondary necessities. Keywords : Type of Merchandise, Working Hours, Business Capital, Income